Neonatal immune challenge followed by adult immune challenge induces epigenetic-susceptibility to aggravated visceral hypersensitivity - Aguirre, Jose E (Neurogastroenterol Motil, 2017)
BACKGROUND: Abdominal pain is one of the major symptoms of inflammatory Bowel Disease (IBD). The inflammatory mediators released by colon inflammation are known to sensitize the afferent neurons, which is one of the contributors to abdominal pain. However, not all IBD patients have abdominal pain, and some patients report abdominal pain during remission, suggesting contributions of other pathological factors to abdominal pain in IBD. Epidemiological studies found early-life gastrointestinal infections a risk factor for IBD symptoms and adult-life gastrointestinal infections may trigger the onset of IBD. We investigated the hypothesis that neonatal colon immune challenge followed by an adult colon immune challenge upregulates spinal cord BDNF that aggravates visceral sensitivity over and above that induced by adult colon immune challenge alone. METHODS: We induced neonatal and adult colon immune challenges by intraluminal administration of trinitrobenzene sulfonic acid to the rat colon. RESULTS: We found that neonatal immune challenge triggers epigenetic programming that upregulates tyrosine hydroxylase in the locus ceruleus when these rats are subjected to an adult colon immune challenge. The upregulation of locus ceruleus tyrosine hydroxylase, upregulates norepinephrine in the cerebrospinal fluid that acts on adrenergic receptors to enhance pCREB binding to the cAMP response element, which recruits histone acetylene transferase (HAT) to the BDNF gene to enhance its transcription resulting in aggravated visceromotor response to colorectal distension. HAT and adrenergic receptor antagonists block the aggravation of visceral sensitivity. CONCLUSION: HAT and adrenergic receptor inhibitors may serve as alternates to opioids and NSAIDS in suppressing abdominal pain in IBD.